2012
DOI: 10.4103/0019-5413.93675
|View full text |Cite
|
Sign up to set email alerts
|

Radiography and sonography of clubfoot: A comparative Study

Abstract: Background:Congenital talipes equinovarus is a common foot deformity afflicting children with reported incidence varying from 0.9/1000 to 7/1000 in various populations. The success reported with Ponseti method when started at an early age requires an imaging modality to quantitate the deformity. Sonography being a radiation free, easily available non-invasive imaging has been investigated for this purpose. Various studies have described the sonographic anatomy of normal neonatal foot and clubfoot and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 14 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…Ponseti method of clubfoot treatment should be applied to patient as soon as possible. It is also important to create a comfortable environment for the child and his family during the manipulation and casting processes [14][15].…”
Section: The Methods Of Congenital Clubfoot Treatment By Ponsetimentioning
confidence: 99%
“…Ponseti method of clubfoot treatment should be applied to patient as soon as possible. It is also important to create a comfortable environment for the child and his family during the manipulation and casting processes [14][15].…”
Section: The Methods Of Congenital Clubfoot Treatment By Ponsetimentioning
confidence: 99%
“…This distance is termed as Medial Malleolus-Navicular Distance (MM-N Distance). Echogenic band termed as "gristle" 18,19 is observed between medial malleolus and navicular as shown in Figure 2. Medial displacement of navicular in relation to the head the talus is scored on a 3 grade scale as shown in Table 1.…”
Section: Medial Projectionmentioning
confidence: 99%
“…Various studies have been performed for sonographic examination of clubfoot. [6][7][8][9][10][11][12][13][14][15][16][17][18] Descriptive assessment of the alignment of various cartilaginous anlage, comparing clinical or radiological assessment with sonography, classification of the deformity. Work on quantification of the deformity either angular or linear, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Medical practitioners require the ability to perform precise measurements of the foot so that they can assess the nature of the deformity, develop a suitable treatment plan and assess the extent to which a current intervention approach is yielding the expected results. 7 The classification methods that are typically employed to measure the level of deformity of clubfoot are those that were developed by Ponseti and Smoley, 8 Harrold and Walker, 9 Catterall, 10 Dimeglio et al 11 and Pirani et al 12 Bhargava et al 13 demonstrated a method of measuring clubfoot deformities and grading them using sonography. While this method may be particularly effective with children who have larger amounts of body fat, the costs associated with performing sonographs are prohibitive.…”
Section: Introductionmentioning
confidence: 99%